EVALUASI PELAKSANAAN PROGRAM PENGENDALIAN HIPERTENSI DI DINAS KESEHATAN KABUPATEN ROKAN HULU TAHUN 2022 : TANTANGAN DAN UPAYA MENINGKATKAN CAPAIAN - Yeni, Gusnita; Lita, Lita; Asmarwiat, Septieni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Hypertension sufferers need health services and early detection so that it does not get worse and cause other disease complications. To prevent this, one way is to improve health services according to community standards. However, the achievement of the hypertension control program in Rokan Hulu Regency in 2022, namely 33.40%, has not yet reached the target (100%). The aim of this research is to evaluate the implementation of the hypertension control program at the Rokan Hulu District Health Service, so that challenges and efforts to improve further achievements are identified. This research method is descriptive qualitative with a case study design, with 4 informants. Determining informants in this research using purposive sampling technique. Data collection was carried out using in-depth interviews, observation and document searching. The results of the research explain that the challenges faced in implementing the program are seen from the input components, namely untrained officers, limited budget allocation and unavailability of KIE media, process components, namely planning which is tied to operational guidelines, limited monitoring and evaluation activities on achievements, lack of coordination with cross-program and lack of cross-sector support which has an impact on the output component, namely program achievements are still low. The conclusion from the results of this research is that the implementation of the hypertension control program at the Rokan Hulu District Health Service in 2022 is still not optimal. The suggestion from the results of this research is that officers carry out On the Job Training, integrated with cross-programs, improve the implementation of monitoring and evaluation, provide rewards for health centers with the best achievements, conveying the results of achievements to the Head of the Health Service to be conveyed to the Regional Head (Regent), carrying out advocacy and outreach to hospitals to collaborate and support the achievement of SPM service targets, as well as increasing coordination with cross-sectors.Keywords: Program Evaluation, Hypertension, Challenges, Efforts